FEMINISME DALAM PROSA LAMA â€œTJERITA NJI PAINAâ€ KARANGAN H. KOOMER - Andri R.M, Laura (Faculty of Humanities, Diponegoro University, 2015)
â€œTjerita Nji Painaâ€ was written during the Dutch Colonial period in Indonesia in 1900. In the work of H. Kommer, â€œTjerita Nji Painaâ€ is appeared differently compared to the other writting on gender similar issues at the same era. The authorâ€™s strong simphaty and compassion to â€nyaiâ€ destiny has ameliorated the negative image of concubine life system in the Dutch Kolonial era. This literature work has clearly shown the braveness of a Dutch Indies woman in dealing with unfairness she faced in her inferior position. Her consiousness on the existent that she was under pressure of patriarchy superiority power has pushed her to struggle to be equal to men. The aim of this research is to unshield ideas fighting the patriarchy system in the community. Other, it pictured the womenâ€™s efforts to come out from the negative stereotipe that show them as weak and powerless. This research is conducted using feminist literary criticism approach in descriptive qualitative methods.